MENGUNGKAP KESADARAN ISLAMI PARA AKADEMISI DALAM MENGEDUKASI RIBA PADA PROSES PEMBELAJARAN AKUNTANSI GUNA PENGAMBILAN KEPUTUSAN SIKAP PROFESI AKUNTAN - Muhammad Rifqul Arif; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACT This study aims to: 1) Know how the influence of Islamic awareness of Academics on decision-making attitude of prospective accountants. 2) Knowing how the influence of Riba education on the decision-making attitude of prospective Accountants. 3) Knowing how the influence of Islamic awareness interaction from Riba education on the decision making attitude of prospective Accountants. The data used in this study are primary data. While the samples were taken using questionnaire with purposive sampling which was then analyzed using multiple regression with moderating variables. The results of this study indicate that each Islamic awareness and usury education has a significant effect on the attitude of the accountant profession, but if Islamic awareness is coupled with usury education as a moderating variable the results are not influential so usury education is not a moderating variable, it can be an independent variable or intervening variable. The results of this study are expected to be a reference for further research and become a consideration for academics, practitioners and knowledge carriers. Keywords: Accounting Education, Islamic Awareness, Usury Education and Decision Making